Two mechanisms regulate keratin K15 expression in keratinocytes: role of PKC/AP-1 and FOXM1 mediated signalling. - Amrita Bose; Muy-Teck Teh; Iain L Hutchison; Hong Wan; Irene M Leigh; Ahmad Waseem (PLoS ONE)
Background Keratin 15 (K15) is a type I keratin that is used as a marker of stem cells. Its expression is restricted to the basal layer of stratified epithelia, and the bulge in hair follicles. However, in certain clinical situations including oral lichen planus, K15 is induced in suprabasal layers, which is inconsistent with the role of a stem cell marker. This study provides insights into the mechanisms of K15 expression in the basal and differentiating keratinocytes. Methodology/principal findings Human keratinocytes were differentiated by three different methods; suspension in methylcellulose, high cell density and treatment with phorbol ester. The expression of mRNA was determined by quantitative PCR and protein by western blotting and immunostaining. Keratinocytes in suspension suppressed β1-integrin expression, induced differentiation-specific markers and K15, whereas FOXM1 (a cell cycle regulated protein) and K14 were downregulated. Rescuing β1-integrin by either fibronectin or the arginine-glycine-aspartate peptide suppressed K15 but induced K14 and FOXM1 expression. Specific inhibition of PKCδ, by siRNA, and AP-1 transcription factor, by TAM67 (dominant negative c-Jun), suppressed K15 expression, suggesting that PKC/AP-1 pathway plays a role in the differentiation-specific expression of K15. The basal cell-specific K15 expression may involve FOXM1 because ectopic expression of the latter is known to induce K15. Using chromatin immunoprecipitation, we have identified a single FOXM1 binding motif in the K15 promoter. Conclusions/significance The data suggests that K15 is induced during terminal differentiation mediated by the down regulation of β1-integrin. However, this cannot be the mechanism of basal/stem cell-specific K15 expression in stratified epithelia, because basal keratinocytes do not undergo terminal differentiation. We propose that there are two mechanisms regulating K15 expression in stratified epithelia; differentiation-specific involving PKC/AP-1 pathway, and basal-specific mediated by FOXM1, and therefore the use of K15 expression as a marker of stem cells must be viewed with caution.